2002
DOI: 10.4049/jimmunol.168.10.4827
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Requirement for IL-15 in the Generation of Primary and Memory Antigen-Specific CD8 T Cells

Abstract: IL-15 and IL-15Rα are required for generation of memory-phenotype CD8 T cells in unimmunized mice. However, the role of IL-15 in primary expansion and generation of Ag-specific memory CD8 T cells in vivo has not been investigated. We characterized the CD8 T cell response against vesicular stomatitis virus (VSV) in IL-15−/− and IL-15Rα−/− mice. Surprisingly, IL-15 was required for primary expansion of VSV-specific CD8 T cells. The generation of VSV-specific memory CD8 T cells was also impaired without IL-15 sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
449
6
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 466 publications
(477 citation statements)
references
References 25 publications
21
449
6
1
Order By: Relevance
“…Previous work has also shown that under certain conditions only long-term maintenance of effector/memory-phenotype CD44 high CD8 + T cells is controlled by IL-15 [20]. After infection with VSV, the clonal expansion of tetramer-positive VSV-specific CD8 + T cells was strikingly decreased in IL-15 -/-mice [41].…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Previous work has also shown that under certain conditions only long-term maintenance of effector/memory-phenotype CD44 high CD8 + T cells is controlled by IL-15 [20]. After infection with VSV, the clonal expansion of tetramer-positive VSV-specific CD8 + T cells was strikingly decreased in IL-15 -/-mice [41].…”
Section: Discussionmentioning
confidence: 90%
“…In accordance with the importance of CD8 + T cells for protection against a number of pathogens, IL-15 was shown to improve the proliferation of memory/effector CD8 + T cells and protective CD8 + T cell-mediated immune responses such as IFN-c production and cytotoxicity [37][38][39]. For example, a deficiency in IL-15 or IL-15Ra led to an impaired CD8 + T cell-mediated immune response and decreased protection from infection with herpes simplex virus type 2 [21,40], vesicular stomatitis virus (VSV) [41], vaccinia virus [18] or Toxoplasma gondii [42]. However, in some cases the role of IL-15 appeared to be redundant since IL-15 -/-mice proved capable of developing protective immune responses after infection with gamma herpes virus 68 [43], lymphocytic choriomeningitis virus [20] or T. gondii [44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is believed that CD8 + memory T cells can persist without MHC class I [209]. However, CD8 + memory T cell survival depends on IL-15 in a normal host, and also depends on IL-7 in a lymphopenic host or in an IL-15 deficient host [169,[210][211][212][213]. CD4 + memory T cell survival and homeostatic proliferation depend on IL-7 signal and also require TCR/MHC class II interaction.…”
Section: Memory Phase Of Cd8 + T Cell Immune Re-sponsementioning
confidence: 99%